PENGGUNAAN LABORATORIUM VIRTUAL BERBASIS SIMULASI PhET UNTUK MENENTUKAN WAKTU PARUH - Marlina, Venny (EduFisika: Jurnal Pendidikan Fisika, 2022)
PhET Simulation is a learning tool that transforms series of experiments into multimedia-based interactive software that can simulate laboratory activities, enabling users to use practical tools in real laboratories. The aim of this research was to determine the decay rates of the isotopes carbon-14 and uranium-238 during their first, second, and third half-lives, as well as to determine the accuracy of the experiments performed in PhET simulations. The method used is an experimental method using a virtual lab with PhET simulations. The research results obtained are that the PhET simulation has a high level of accuracy. The accuracy of the 14C isotope experiment is 96.47%. The accuracy of the isotope 238U is 94.77%. Therefore, a PhET simulation-based virtual laboratory to calculate half-lives can be used as a relevant learning media solution to explain the decay of carbon-14 and uranium-238 isotopes, thus prioritizing modern abstract physics that can be analyzed and observed so that it becomes interesting to study.